2016
DOI: 10.7150/ijbs.14430
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNA: Recent Updates in Atherosclerosis

Abstract: Long noncoding RNAs belong to a class of noncoding RNAs longer than 200 nucleotides with the epigenetic regulation potential. As a novel molecular regulator, lncRNAs are often dysregulated in various pathological conditions and display multiple functions in a wide range of biological processes. Given that recent studies have indicated that lncRNAs are involved in atherosclerosis-related smooth muscle cell, endothelial cell, macrophage and lipid metabolism regulation, it is pertinent to understand the potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
0
8

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(82 citation statements)
references
References 91 publications
0
74
0
8
Order By: Relevance
“…Among yet, microRNAs (miRNAs) have been extensively studied, while little is known about the role of long ncRNAs (lncRNAs). Recent studies have partially revealed the regulatory functions of lncRNAs in complex human diseases, such as a variety of cancers [7], neurological disorder [8] and atherosclerosis [9]. Further investigations indicate that lncRNAs may regulate the biological processes of atherosclerosis-related endothelial cells, especially angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Among yet, microRNAs (miRNAs) have been extensively studied, while little is known about the role of long ncRNAs (lncRNAs). Recent studies have partially revealed the regulatory functions of lncRNAs in complex human diseases, such as a variety of cancers [7], neurological disorder [8] and atherosclerosis [9]. Further investigations indicate that lncRNAs may regulate the biological processes of atherosclerosis-related endothelial cells, especially angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…LncRNA has also been shown to be involved in pathological vascular conditions such as atherosclerosis [58], microvascular disorders [59], diabetic retinopathies [60], pulmonary hypertension [61], and myocardial infarction [62]. LncRNA ANRIL is transcribed from INK/ARF locus, which is expressed in atherosclerotic tissues and cells such as primary coronary smooth muscle cells, vascular endothelial cells, human monocyte-derived macrophage cells, and carotid myocytes [59].…”
Section: Lncrna and Vascular Pathologiesmentioning
confidence: 99%
“…LncRNAs have a poorly conserved primary structure but relatively well‐conserved secondary structure and splicing . The mechanisms of action of lncRNAs are diverse and not yet fully understand, but mainly include genetic imprinting, chromatin remodeling, cell cycle regulation, splicing regulation, mRNA degradation and translation regulation . LncRNAs have been shown to control every level of the regulation of the gene expression pathway .…”
Section: Lncrnas and Their Mechanisms Of Actionmentioning
confidence: 99%
“…26,27 The mechanisms of action of lncRNAs are diverse and not yet fully understand, but mainly include genetic imprinting, chromatin remodeling, cell cycle regulation, splicing regulation, mRNA degradation and translation regulation. 28,29 LncRNAs have been shown to control every level of the regulation of the gene expression pathway. 24 An overview of the cellular functions of lncRNAs is shown in Figure 1.…”
Section: Lncrnas and Their Mechanisms Of Actionmentioning
confidence: 99%